Optimizing Licensing Supervision through Online Single Submission to Support Salted Fish Trading MSMEs - Rohmatun Uyun; Nunik Nurhayati (Proceeding International Conference Restructuring and Transforming Law, 2025)
This study aims to explain the challenges in risk-based business licensing supervision for micro, small, and medium enterprises (MSMEs/UMKM) engaged in salted fish trading, as well as strategies to optimize such supervision. Employing a normative approach, the research analyzes relevant laws and regulations governing risk-based licensing for MSMEs. The findings indicate that the supervision of risk-based licensing for salted fish trader MSMEs is governed by Law No. 6 of 2023 and Government Regulation No. 5 of 2021, which streamline licensing through the Business Identification Number (NIB) via the Online Single Submission (OSS) system. However, several challenges persist, including limited understanding among business actors, insufficient human resources and technology (Articles 230 & 310 of PP No. 5/2021), and weak inter-stakeholder coordination (Articles 15 & 231 of PP No. 5/2021). Although local governments are mandated to provide assistance (Article 227 of PP No. 5/2021), the lack of outreach efforts hampers MSME compliance. Optimization strategies should involve cross-sectoral synergy, the utilization of technology, and enhanced education for business actors to ensure regulatory compliance, improve competitiveness, and foster sustainable business development.